Characteristics of Drivers' Lane Choice at Large Multi-lane Roundabout - Mee Chong, Elizabeth Eu; Saif Al-Mamari, Rahma Naser (International Journal of Integrated Engineering, 2020)
The use of modern roundabout as an intersection treatment is a popular choice. To increase the capacity, large multi-lane roundabout has been implemented to solve traffic congestions. Comparatively to small single-lane roundabouts, where many studies have been devoted to, the maneuver at multi-lane roundabout is a highly complex situation due to drivers' behavior in lane choosing. Little is known on the drivers' behavior at large multilane roundabouts. This paper aims to explore the drivers' lane choice behavior and its impact on the performance of large multi-lane roundabout. Traffic data were collected at three-lane roundabout on a normal day at peak traffic hours by using voice recorders and video cameras. Drivers' behavior had been characterized by assessing their lane choices from entry lanes to circulating lanes and from circulating lanes to exit lanes. Two models of drivers' lane choices were generated, the first representing reality and the second depicting standard roundabout lane discipline. Both models had been analyzed by using SIDRA Intersection software. Resultsindicated that the large number of lanes provides high freedom for drivers on their behavior which cannot be fully controlled. Also, drivers tend to follow the natural movement path to go through the roundabout correctly. Lane discipline marking is effective for multi-lane roundabout especially for roundabout with equal number of entry and circulating lanes in improving the traffic performance.